How can we evaluate the potential of innovative vaccine products and technologies in resource constrained settings? A total systems effectiveness (TSE) approach to decision-making. (11th December 2020) - Botwright, Siobhan; Kahn, Anna-Lea; Hutubessy, Raymond; Lydon, Patrick; Biey, Joseph; Karim Sidibe, Abdoul; Diarra, Ibrahima; Nadjib, Mardiati; Suwantika, Auliya A.; Setiawan, Ery; Archer, Rachel; Kristensen, Debra; et al.
Abstract: Innovations in vaccine product attributes could play an important role in addressing coverage and equity (C&E) gaps, but there is currently a poor understanding of the full system impact and trade-offs associated with investing in such technologies, both from the perspective of national immunisation programmes (NIPs) and vaccine developers. Total Systems Effectiveness (TSE) was developed as an approach to evaluate vaccines with different product attributes from a systems perspective, in order to analyse and compare the value of innovative vaccine products in different settings. The TSE approach has been advanced over the years by various stakeholders including the Bill and Melinda Gates Foundation (BMGF), Gavi, PATH, UNICEF and WHO. WHO further developed the TSE approach to incorporate the country perspective into immunisation decision-making, in order for countries to evaluate innovative products for introduction and product switch decisions, and for vaccine development stakeholders to conduct their assessments of product value in line with country preferences. This paper describes the original TSE approach, development of the tool and processes for NIPs to apply the WHO TSE approach, and results from piloting in 12 countries across Africa, Asia and the Americas. The WHO TSE framework emerged from this piloting effort. The WHO TSE approach has been welcomed by NIP and vaccine development stakeholders as a useful tool to evaluate trade-offs between different products. It was emphasised that the concept of "total systems effectiveness" is likely to be context-specific and that TSE is valuable in facilitating a deliberative process to articulate NIP priorities, for decisions around product choice, and for prioritising the development of future vaccine innovations.